2008
DOI: 10.2478/v10042-008-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelets augment respiratory burst in neutrophils activated by selected species of gram-positive or gram-negative bacteria.

Abstract: Neutrophils and platelets circulate in blood system and play important physiological roles as part of immunological system. Neutrophils are the first line of host defense against various intruders, and platelets are satellite cells cooperating with other components of defense system. Recent studies report about the cooperation among these types of cells. We analyzed the effect of platelets on oxygen burst in neutrophils triggered by Staphylococcus aureus and Escherichia coli bacteria in vitro. The effect of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…In line with our findings, it has also been reported that S. aureus triggers CD11b upregulation and oxidative burst (40). Furthermore, phagocytosis was recently implicated as a crucial event of the innate immune response to S. aureus (22,41).…”
Section: Discussionsupporting
confidence: 92%
“…In line with our findings, it has also been reported that S. aureus triggers CD11b upregulation and oxidative burst (40). Furthermore, phagocytosis was recently implicated as a crucial event of the innate immune response to S. aureus (22,41).…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that MAP kinase pathways are in play in COX-2 and PGE 2 production, but not IL-6 expression in these cells. In related studies, platelets have been shown to enhance neutrophil oxidative burst in response to Gram-positive as well as Gram-negative bacteria [42]. Moreover, Bennett et al demonstrated that platelets participate in the regulation of B- and T-lymphocyte- and immunoglobulin-mediated immune responses via CD40/ligand–CD40 interactions [9].…”
Section: Platelets: the Other White Cellsmentioning
confidence: 99%
“…Platelets, which bind more avidly to the endothelium after TLR4 stimulation, can snare neutrophils via P-selectin-PSGL-1 interactions, allowing for secondary interactions between neutrophils and the endothelium via lymphocyte function-associated antigen 1. In addition to enhancing neutrophil recruitment into infected tissues, platelets also enhance the bactericidal activity of neutrophils by increasing levels of TNF (7,28,77) and by secreting IL-1␤ (46) and thromboxane A 2 (TXA 2 ), which enhances the respiratory burst activity of neutrophils (56). Antibody blockade of P-selectin decreases neutrophil infiltration and bacterial clearance in a rat model of cecal ligation and puncture (CLP) (64), supporting an in vivo role for platelet P-selectin in host defense.…”
Section: Plateletsmentioning
confidence: 99%